EFFECT OF CURCUMIN AND NANOCURCUMIN ON HEAMATO BIOCHEMICAL PARAMETERS IN DALTON’S ASCITES LYMPHOMA IN MICE - P. Krishnaveni; M. Thangapandiyan; P. Raja; G.V.S Rao (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Curcumin derived from curcuma longa has been reported for its anti-cancer activity, but low bioavailability limits the therapeutic potential of curcumin. In this study curcumin and solid lipid nanocurcumin were tested for its therapeutic use and methotrexate was used as the standard drug. Methotrexate at a dose rate of 3.5mg/kg bodyweight and curcumin and nanocurcumin at a dose rate of 100 and 50 mg/kg bodyweight were evaluated in Dalton’s Ascites Lymphoma-bearing mice by assessing various hematobiochemical parameters. Hematological parameters were estimated using auto hematology analyzer and biochemical parameters with automatic serum biochemical analyzer.   Dalton’s Ascites Lymphoma-bearing mice showed reduction in RBC count and amount of Hb and increased leukocyte count with neutrophilia in comparison with normal control group. The tumor control group also showed elevated levels of ALT, AST and ALP while albumin and total protein levels decreased in serum. Treatment with curcumin and nanocurcumin showed significant increase in RBC and Hb count as well as decrease in WBC count. There was a significant decrease ALT, AST and ALP and increase in albumin and total protein levels. Precisely curcumin and nanocurcumin showed significant influence in the restoration of various hematobiochemical parameters.